Achievement of high energy carbon based supercapacitors in acid solution enabled by the balance of SSA with abundant micropores and conductivity. (1st September 2020) - Tang, Lujie; Ji, Xu; Wu, Peng; Luo, Haowei; Zhu, Yuanyuan; Deng, Liyu; Cheng, Shuang; Liu, Meilin
Abstract: Wide potential window and stable current collector that are high concerned with the energy density and durability respectively of an aqueous based energy storage device have always been big challenges. Herein, flexible and self-standing carbon fiber fabric with high surface area of 951 m 2 g −1 and high conductivity (HSHC-CFF) are synthesized via a facile heat treatment process. When served as supercapacitive electrode directly in 1 M H2 SO4, a high specific capacitance of 255 F g −1 (3.32 F cm −2, 127.7 F cm −3 ) at 0.5 A g −1 is achieved, which means a high area normalized capacitance of 26 μF cm −2 that is in the range of theoretical values speculated from the electric double-layer mechanism is realized. Importantly, operation window of the HSHC-CFF film is high close to 1.8 V (−0.6–1.2/1.15 V vs Ag/AgCl), resulting in a high energy density of 16 Wh kg −1 at 160 W kg −1 for a symmetric cell when considering the mass of two electrodes. Meanwhile, the high performance is maintained and even better along cycling of over 20, 000 cycles (the capacitance rises to 118% of the initial value). A mechanism of micropore (∼0.7 nm) induced dehydration process of electrolyte cations and linear counter-ions' accommodation in the pores is proposed, which is supposed to contribute to the high normalized capacitance and wide operation window. Graphical abstract: Image 1 Hightlights: HSHC-CFF exhibits wide window of 1.8 V in 1M H2 SO4 (−0.6–1.2 V vs Ag/AgCl). High specific capacitance of 255 F g −1 at 0.5 A g −1 is achieved for the HSHC-CFF. Dehydration process of electrolyte ions induced by micropores (∼0.7 nm) is proposed.